Perhitungan Debit Koagulan Poly Aluminium Chloride (PAC) Yang Diinjeksikan Pada Air Baku Proses Pengolahan Air PT. X - Ratna Kristina Tarigan (JURNAL VOKASI TEKNIK, 2024)
Poly Aluminum Chloride is a chemical used to reduce water turbidity. Poly Aluminum Chloride will agglomerate dirt in water into larger particles so that it settles more easily. The amount of coagulant added to the water must be precise so that the turbidity of the water can be suppressed to the maximum. To find out the optimal dose, a jar test procedure was carried out. The jar test was carried out by adding coagulants with different variations. The jar test will give results on how variations in the amount of coagulant affect the turbidity level of the water. In water with a turbidity of 25.2 NTU, the optimum dose of PAC coagulant used was 30 ppm. With this dose, the PAC coagulant discharge injected into raw water at a water treatment plant is 56,0747 ml/s.